2017
DOI: 10.14715/cmb/2017.63.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide levels in response to the patients with different stage of diabetes

Abstract: The association between hyperglycaemia and serum nitric oxide (NO) levels has not yet been fully clarified. Thus, it was aimed to evaluate the concentration of NO metabolites (nitrate, nitrite) in diabetic patients and to find the relationship between hyperglycaemia and serum NO levels in diabetic and prediabetic patients, and control groups. In this study, 100 subjects were divided into 3 groups: healthy control (n=20), prediabetic (n=40) and diabetic (n=40). Glycemic control was assessed using glycated hemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Their findings were in agreement with the observations of [42,43]. More recently, Ozcelik and Algul [44] also found higher NO levels in not only diabetics but prediabetics as well.…”
Section: Nitric Oxidesupporting
confidence: 90%
“…Their findings were in agreement with the observations of [42,43]. More recently, Ozcelik and Algul [44] also found higher NO levels in not only diabetics but prediabetics as well.…”
Section: Nitric Oxidesupporting
confidence: 90%
“…Increase (Assmann et al., ; Ozcelik & Algul, ), decrease (Khalifi et al., ), and no change (Schmetterer et al., ) of serum NOx levels have been reported in diabetes. Two months administration of nitrate increased NOx levels to near those of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Increase (Assmann et al, 2016;Ozcelik & Algul, 2017), decrease (Khalifi et al, 2015), and no change (Schmetterer et al, 1997) Peleli et al, 2016). One study showed increased serum NOx levels following nitrate supplementation in diabetic rats after 8 weeks (Khalifi et al, 2015); in another study, serum nitrate levels on day 42 in nitrate-treated diabetic rats were lower than in nitratetreated controls (Gheibi et al, 2018).…”
Section: Ta B L E 3 Effect Of Sodium Nitrate On the Sperm Parameters mentioning
confidence: 99%
“…The COX2 and NOS3 gene polymorphisms alter COX2 and NOS3 gene expression, as well as cyclooxygenase and nitric oxide synthesis. Cyclooxygenase and nitric oxide are important mediators of the inflammatory response in diabetes . Low grade inflammation has been shown to play a significant role in the pathogenesis of GDM …”
Section: Discussionmentioning
confidence: 99%
“…Cyclooxygenase and nitric oxide are important mediators of the inflammatory response in diabetes. [23][24][25][26][27] Low grade inflammation has been shown to play a significant role in the pathogenesis of GDM. [3][4][5] Apgar (0-10) 9.9 ± 0.4 9.7 ± 1.0…”
Section: Discussionmentioning
confidence: 99%